2021
DOI: 10.1038/s41598-021-94314-1
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular NLRP3 inflammasome particles are internalized by human coronary artery smooth muscle cells and induce pro-atherogenic effects

Abstract: Inflammation driven by intracellular activation of the NLRP3 inflammasome is involved in the pathogenesis of a variety of diseases including vascular pathologies. Inflammasome specks are released into the extracellular compartment from disrupting pyroptotic cells. The potential uptake and function of extracellular NLRP3 inflammasomes in human coronary artery smooth muscle cells (HCASMC) are unknown. Fluorescently labeled NLRP3 inflammasome particles were isolated from a mutant NLRP3-YFP cell line and used to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…In contrast to other types of cell death, such as necrosis and apoptosis, pyroptosis causes the rupture of the cell membrane via pores formation and induces the release of mature inflammatory cytokines, damage associated molecular patterns (DAMPs) and NLRP3 inflammasome specks into the extracellular compartment where they remain active, ultimately resulting in an amplification of the inflammatory response [ 20 , 21 , 22 ]. Pyroptosis may be a physiologic process during the acute inflammatory response by maintaining cell homeostasis and preventing excessive cell proliferation, but under chronic disease conditions, it will lead to uncontrolled inflammation, excessive cell death and tissue remodeling [ 23 , 24 ].…”
Section: The Nlrp3 Inflammasomementioning
confidence: 99%
“…In contrast to other types of cell death, such as necrosis and apoptosis, pyroptosis causes the rupture of the cell membrane via pores formation and induces the release of mature inflammatory cytokines, damage associated molecular patterns (DAMPs) and NLRP3 inflammasome specks into the extracellular compartment where they remain active, ultimately resulting in an amplification of the inflammatory response [ 20 , 21 , 22 ]. Pyroptosis may be a physiologic process during the acute inflammatory response by maintaining cell homeostasis and preventing excessive cell proliferation, but under chronic disease conditions, it will lead to uncontrolled inflammation, excessive cell death and tissue remodeling [ 23 , 24 ].…”
Section: The Nlrp3 Inflammasomementioning
confidence: 99%
“…These data identify extracellular inflammasome particles as a mechanism that mediates inflammation from the site of damaged tissue to the endothelium. Previous findings of our group demonstrated that extracellular NLRP3 particles are also ingested by human coronary artery smooth muscle cells and macrophages where they induce pro-inflammatory and atherogenic signaling by increasing the extracellular matrix production, promoting the secretion of pro-atherogenic and inflammatory cytokines and cell migration ( Gaul et al, 2021 ).…”
Section: Discussionmentioning
confidence: 91%
“…Extensive exercise with a high mechanical muscular load can mediate systemic inflammation via the release of extracellular inflammasome complexes. We and others propose that these pyroptosis-derived NLRP3 inflammasome particles exert pro-atherogenic effects ( Gaul et al, 2021 ; Sun et al, 2021 ).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations